Raising young learners’ ELF-awareness: An intercultural telecollaboration between Italian and Kyrgyz students - Grazzi, Enrico; Kozlova, Tatiana (Status Quaestionis, 2023)
This article provides an overview of the strategies aimed at raising young learners’ awareness of English as a lingua franca (ELF), in order to reflect, in language pedagogy, on the profound transformation that English has undergone in recent decades. The main purpose of our research is to explore the efficiency of innovative intercultural activities like telecollaboration in developing young learners’ intercultural communicative competence (ICC) and ELF-awareness. For the purposes of this research, a project entitled Intercultural telecollaboration: Italy-Kyrgyzstan was conducted by the authors during the school year 2022-2023. This study involved the design and implementation of web-mediated collaborative tasks for an international community of practice (CoP) of young learners, which comprised twenty-six Italian and fourteen Kyrgyz same age pupils (10-11 years old). We concluded that a blended approach that combines ELF and sociocultural theory (SCT) should be integrated into young learners’ English syllabus and should become an integral part of teacher education programmes.